Transforming growth factor‐beta1 and myeloid‐derived suppressor cells: A cancerous partnership. Issue 1 (8th April 2021) - Mojsilovic, Slavko; Mojsilovic, Sonja S.; Bjelica, Suncica; Santibanez, Juan F.
Abstract: Transforming growth factor‐beta1 (TGF‐β1) plays a crucial role in tumor progression. It can inhibit early cancer stages but promotes tumor growth and development at the late stages of tumorigenesis. TGF‐β1 has a potent immunosuppressive function within the tumor microenvironment that largely contributes to tumor cells' immune escape and reduction in cancer immunotherapy responses. Likewise, myeloid‐derived suppressor cells (MDSCs) have been postulated as leading tumor promoters and a hallmark of cancer immune evasion mechanisms. This review attempts to analyze the prominent roles of both TGF‐β1 and MDSCs and their interplay in cancer immunity. Furthermore, therapies against either TGF‐β1 or MDSCs, and their potential synergistic combination with immunotherapies are discussed. Simultaneous TGF‐β1 and MDSCs inhibition suggest a potential improvement in immunotherapy or subverted tumor immune resistance. Key Findings: TGF‐β1; MDSCs; myeloid‐derived suppressor cells; T‐cell immunosuppression; tumor progression; cancer